Fuzzy AHP Approach in Handling Returns Product of Bottle Glass Mineral Water at PT Marina - Sesar Husen Santosa; Agung Prayudha Hidayat; Ridwan Siskandar; Annisa Rizkiriani; Khoirul Aziz Husyairi (Jurnal Sains dan Teknologi: Jurnal Keilmuan dan Aplikasi Teknologi Industri, 2024)
PT Marina is a company engaged in bottled mineral water production, where one of its products is glass packaging. The fluctuating demand for glass bottled drinking water products causes companies to plan optimal production. Based on the results of image scanning using the SCAPSA application, it was found that the total return was 2193 glasses in December 2024. Based on the identification results using the Pareto diagram method, it was found that the highest product return from consumers was needle leaks, namely 895 glasses. The identification results indicate priority improvements that will be carried out using the Fuzzy AHP method with triangular fuzzy numbers. At the actor level, the highest normalization result was obtained for the production section with a defuzzification value of 0.78. At the factor level, the highest normalization was obtained for the quality of the glass packaging with a defuzzification value of 0.49. Hence, the optimal tension temperature setting on the felling machine was an alternative improvement for returning leaking needles with a defuzzification value of 0.55 and a consistency index of 0.03. Based on the results of the improvements, it was found that the company could reduce returns on products by 85.70% to 128 glasses.